2013
DOI: 10.1021/jp402477q
|View full text |Cite
|
Sign up to set email alerts
|

Anchoring Energy Acceptors to Nanostructured ZrO2 Enhances Photon Upconversion by Sensitized Triplet–Triplet Annihilation Under Simulated Solar Flux

Abstract: Photon upconversion by sensitized triplet−triplet annihilation (UC-STTA) is a promising strategy for boosting the theoretical maximum efficiency of single threshold solar cells, in particular, dye-sensitized solar cells (DSSCs). Here, we report a substantial increase in the efficiency of UC-STTA on a nanostructured surface, using noncoherent excitation light with intensities as low as 0.5 mW cm −2 , easily achieved under sun illumination. The studied surface was a mesoporous ZrO 2 film working as a proxy syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
92
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(96 citation statements)
references
References 48 publications
4
92
0
Order By: Relevance
“…S8.2). As discussed by Lissau et al 24 , this slow onset is due to the necessary build-up of triplet-excited BDCA prior to TTA occurring, which generates the injection-active BDCA singlet state. BDCA + absorption is centred around 700 nm, but is quite broad and featureless, making direct spectral analysis somewhat challenging.…”
Section: Resultsmentioning
confidence: 92%
“…S8.2). As discussed by Lissau et al 24 , this slow onset is due to the necessary build-up of triplet-excited BDCA prior to TTA occurring, which generates the injection-active BDCA singlet state. BDCA + absorption is centred around 700 nm, but is quite broad and featureless, making direct spectral analysis somewhat challenging.…”
Section: Resultsmentioning
confidence: 92%
“…Lissau et al reported upconverted fluorescence from the PtOEP/DPA system adsorbed onto ZrO 2 nanoparticles, but found their system to be limited by aggregation; sub-optimal dye loading and orientation; and oxygen quenching. An improved system featured functionalized DPA with carboxylate anchor groups on ZrO 2 nanoparticles floating in a butyronitrile solution containing the PtOEP sensitizer, and showed improved performance 144 .…”
Section: Increasing the Molecular Densitymentioning
confidence: 99%
“…Hybrid Surroundings : Lissau et al investigated TTA upconversion in an environment that mimics a dye‐sensitized solar cell. PtOEP in butyronitrile (BuN) solution was used as a sensitizer, while the well‐known emitter DPA was chemically modified to methyl 4‐(10‐p‐tolylanthracen‐9‐yl)benzoate (MTAB) and chemisorbed onto mesoporous ZrO 2 , with subsequent removal of oxygen . Under excitation at (534 ± 5) nm and a very low irradiance of 8 mW cm −2 , they observed an internal UCQY of 0.04% by comparison to Ru(bpy) 3 Cl 2 in air‐equilibrated water as a reference standard.…”
Section: Upconverter Materialsmentioning
confidence: 99%